A STUDY ON BRUCELLOSIS AMONG CAMELS ‎ IN NAJAF-PROVINCE - K.Al-Delaimi‎, A.; H.Ali ‎, A.; A.R.Mohammecd, T. (The Iraqi Journal of Veterinary Medicine, 1988)
There were no available sufficient stuties on brucellosis among camels in our counrty. Thus, the aim of this work was to investigate the prevalence of brucellosis in camels slaughtered for meat purposes in Najaf abattoire. Data for camels in this study was obtained from 515 blood samples collected from both sexes. The serum samples were tested by Rose Benge! Plate test (REPT), serum (tube) agglutination test (TAT) and the slide agglutination test (SAT) using Brucella abortus and Brucella melitensis antigens. The overall results of RBPT, TAT and SAT were 6.6%, 1.74% and 3.1%, 2.3% respectively. The percentage of the females positive reactors was 4.85% to RBPT, 1.35 to the TAT and 2.33, 1.94 to SAT (by Br. abortus antigen and Br. Melitensis antigen). The males have shown lower reactor rates revealed by these test, was 1.74% to RBPT, 0.38% to TAT and 0.77%, 0.38% to SAT. The present study indicate also that SAT could be used as a screening test side by side with the RBPT.